Access to Drinking Water and Sanitation in Africa - Kauffmann, Céline (OECD Development Centre Policy Insights, 2007)
Africa is unlikely to reach the drinking water and sanitation Millennium Development Goals. Disparities among countries are large, and the deficit in sanitation is greater than that for drinking water. Serious reforms in institutions, legal frameworks, and policies are needed